2014
DOI: 10.1159/000368369
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Lung Volume Reduction with Endobronchial Valves in Patients with Severe Emphysema and Established Pulmonary Hypertension

Abstract: Background: One of the most common forms of pulmonary hypertension (PH) is that associated with chronic obstructive pulmonary disease (COPD). So far, patients with severe emphysema and established PH have been excluded from endoscopic lung volume reduction (ELVR) therapy due to the risk of right heart decompensation. Objective: The aim of this pilot study was to evaluate the feasibility and efficacy of ELVR using one-way endobronchial valves (EBV) in this specific group of patients. Methods: We prospectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In the case of severe PH, ELVR with coils, vapor, and sealants should be avoided. In selected cases with PH, EBV placement may be considered following multidisciplinary discussion [12]. Additionally, limited evidence has been published for successful valve treatment in emphysema patients with a FEV 1 < 20% pred.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In the case of severe PH, ELVR with coils, vapor, and sealants should be avoided. In selected cases with PH, EBV placement may be considered following multidisciplinary discussion [12]. Additionally, limited evidence has been published for successful valve treatment in emphysema patients with a FEV 1 < 20% pred.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Available clinical data have shown that EBV treatment benefits patients that are α 1 -antitrypsin deficient [13] , have homogeneous distribution of emphysema [4,9] , have upper or lower lobe predominant emphysema [14] , and have pulmonary hypertension [1,15] . Patients with unstable cardiovascular disease such as severe heart failure (left ventricular ejection fraction <35% despite optimal medical management), unstable cardiac arrhythmia, myocardial infarction, or stroke within the past 6 months should be excluded until stabilized or improved.…”
Section: Medical History and Stabilitymentioning
confidence: 99%
“…When an elevated right ventricular systolic pressure measured by echocardiography (>50 mm Hg) is identified, a right heart catheterization should be undertaken. In selected cases with pulmonary hypertension, endobronchial valve (EBV) placement may be considered following multidisciplinary discussion [9] . In our opinion, if they are excluded from valve placement due to pulmonary hypertension, they should not be considered suitable for any other current interventional or surgical procedures.…”
Section: Patient Selectionmentioning
confidence: 99%